2005
DOI: 10.1063/1.2138368
|View full text |Cite
|
Sign up to set email alerts
|

Direct photofabrication of refractive-index-modulated multimode optical waveguide using photosensitive sol-gel hybrid materials

Abstract: Photosensitive sol-gel hybrid materials ͑hybrimers͒ exhibited a thick film property, an efficient refractive index tunability through the control of their compositions, and a high photosensitivity upon UV exposure. The materials were used for the direct photofabrication of the multimode optical waveguide ͑MOW͒ with a large core structure. Due to the outstanding optical properties of these materials, problems and complexities associated with the fabrication of MOW could be overcome, and a MOW with good propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…To overcome these problems, photosensitive organic-inorganic hybrid materials (known as hybrimers) have been introduced in recent times for the photopatterning of microstructures. [8][9][10][11][12][13][14][15][16] It has been reported that hybrimers containing the photopolymerizable methacryl group can be used to make thick photopatterned and thermally stable films with unique characteristics. 17 The acryl or methacryl groups usually employ UV-curable materials based on free radical polymerization because of their excel-lent reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, photosensitive organic-inorganic hybrid materials (known as hybrimers) have been introduced in recent times for the photopatterning of microstructures. [8][9][10][11][12][13][14][15][16] It has been reported that hybrimers containing the photopolymerizable methacryl group can be used to make thick photopatterned and thermally stable films with unique characteristics. 17 The acryl or methacryl groups usually employ UV-curable materials based on free radical polymerization because of their excel-lent reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Organic−inorganic hybrid materials (hybrimers) which are based on sol−gel derived oligosiloxane have been studied for a diverse range of optical applications including optical waveguides and microlenses. By combining both inorganic and organic characteristics, these materials exhibit high transparency, good thermal stability, and low optical loss/birefringence, as well as being simple to process , . Moreover, by varying the specific organic and inorganic composition, we can easily control the material characteristics such as the dielectric constant and refractive index, making these films interesting for both electronics and optics.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) In particular, inorganic-organic hybrid materials showed high efficiency of photoinduced and thermally induced polymerization upon feasible modification of the organic functional moiety such as photopolymerizable and thermopolymerizable groups in sol-gel processing. [8][9][10] In addition, the inorganic-organic hybrid materials show high optical transparency in the visible-wavelength regions. Therefore, these outstanding inorganic-organic hybrid materials offer great potential as nano-imprinting materials for direct application to microphotonic and nanophotonic devices.…”
Section: Introductionmentioning
confidence: 99%